2013
DOI: 10.2147/copd.s39555
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of COPD and clinical course in patients with unrecognized airflow limitation

Abstract: Chronic obstructive pulmonary disease (COPD) is frequently under-recognized and underdiagnosed. To determine the natural history of recognized and unrecognized COPD, we studied the rate of diagnosis, health care utilization, and mortality in patients with airflow limitation (AFL). Three hundred forty-seven outpatients at the Cincinnati Veterans Administration Medical Center performed spirometry and completed a respiratory questionnaire. Patients were followed for a minimum of 30 months and medical records were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…ED physicians diagnosed COPD in approximately 6% of respondents, which corroborates our previous finding that ED visits often precede a new diagnosis, and that Veterans with undiagnosed COPD had more than twice as many ED visits for respiratory disorders compared with Veterans with previously diagnosed COPD. 44, 45 Thus, the PCP plays an essential role in not only the recognition and diagnosis of COPD but also the communication of the diagnosis of COPD to the patient and ED visits seem to precipitate the diagnosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…ED physicians diagnosed COPD in approximately 6% of respondents, which corroborates our previous finding that ED visits often precede a new diagnosis, and that Veterans with undiagnosed COPD had more than twice as many ED visits for respiratory disorders compared with Veterans with previously diagnosed COPD. 44, 45 Thus, the PCP plays an essential role in not only the recognition and diagnosis of COPD but also the communication of the diagnosis of COPD to the patient and ED visits seem to precipitate the diagnosis of COPD.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32] The main factors associated with underdiagnosis are: younger age, less severe airway obstruction, and few respiratory symptoms. [28][29][30][31][32] The main factors associated with underdiagnosis are: younger age, less severe airway obstruction, and few respiratory symptoms.…”
Section: Justificationmentioning
confidence: 99%
“…[28][29][30][31][32] The main factors associated with underdiagnosis are: younger age, less severe airway obstruction, and few respiratory symptoms. 30,[33][34][35] The absence or mildness of symptoms at this pre-clinical stage of the disease contributes to underdiagnosis. 30,[33][34][35] The absence or mildness of symptoms at this pre-clinical stage of the disease contributes to underdiagnosis.…”
Section: Justificationmentioning
confidence: 99%
“…In Latin America, the PLATINO (the Latin American Project for Investigation of Obstructive Lung Disease) study showed a prevalence of 14.3%, and an under‐diagnosis of 89% . One‐third of patients detected using population‐based studies or case finding approaches in primary care settings are asymptomatic and more than half have mild symptoms …”
Section: Introductionmentioning
confidence: 99%